Brand Image and Customer Retention in Tourism Destinations: The Mediating Role of Customer Satisfaction: Case of Visitors to Mahoni Bangun Sentosa Tourist Destination - maulana dzulqarnain; Lutfi; Yanto Azie Setya (PT Larva Wijaya Penerbit, 2026)
The purpose of this study is to examine the effect of brand image on customer retention with customer satisfaction as a mediating variable, as well as the role of physical evidence, among visitors of Mahoni Bangun Sentosa Tourism. This study employs a quantitative research approach using a survey method. Data were collected from 150 respondents who had visited Mahoni Bangun Sentosa Tourism at least once, selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software to test the proposed hypotheses. The results of this study indicate that: (1) brand image has a positive and significant effect on customer retention; (2) brand image has a positive and significant effect on customer satisfaction; (3) customer satisfaction has a positive and significant effect on customer retention; (4) customer satisfaction is able to mediate the effect of brand image on customer retention; (5) physical evidence has a positive and significant direct effect on customer retention; (6) physical evidence does not moderate the relationship between brand image and customer retention. These findings imply that strengthening brand image and enhancing customer satisfaction are essential strategies to improve customer retention in tourism destinations, while physical evidence serves as a direct supporting factor rather than a moderating variable.